Adventuring in Hawaii : Revised Edition - McMahon, Richard, 1928- (University of Hawaii Press, 2003)
Adventure awaits you in Hawaii! Let Adventuring in Hawaii show you how and where to find it. Here is a comprehensive, up-to-date guide to the many outdoor activities available year-round in the Islands: hiking, backpacking, cycling, mountain biking, snorkeling, scuba diving, surfing, windsurfing, kayaking, hunting, fishing. Covering all six of the main islands, Adventuring in Hawaii is also a complete, stand-alone reference, providing brief overviews of geology, geography, climate, flora, and fauna. It furnishes insights into the history and culture of the Fiftieth State and offers current information on public transportation, campgrounds, beach access, and personal safety. A helpful list of Hawaiian words is included, as well as a mini-directory of addresses, phone numbers, email addresses, and web sites that will help you plan your adventures. For the not-so-active, "Adventuring by Car" sections provide directions to lesser-known but fascinating locales accessible by vehicle. So get out of that beach chair--and take this book with you!